Analysis of phased array antenna system via spherical harmonics decomposition. Issue 18 (1st November 2019) - Famoriji, Oluwole John; Akingbade, Kayode; Ogunti, Erastus; Apena, Waliu; Fadamiro, Akinwale; Lin, Fujiang
Abstract : Spherical phased‐array antenna has hemispherical scan coverage for transmission of satellite imagery data at high bit rates to the ground station. Different conditions have been assigned based on their effects on the overall performance of the communication link. Reliability analysis consequently becomes an important requirement of any system onboard a satellite. Although the phased array and some connected algorithms have been presented in the literatures; however, there is no extensive systematic and theoretical performance evaluation framework formulated. In this work, the authors present new method that efficiently and effectively analyses the statistical performance of phased‐array antenna systems using spherical harmonics expansion approach. Specifically, the errors caused by limited antenna element number, measurement noise of antenna, imprecision in phased‐array antenna elements positioning, and spatial aliasing are systematically and theoretically benchmarked via simulations. Spatial sampling mechanisms for the positioning of array antenna elements on a sphere are presented and evaluated. This study proposed design guide and analysis for spherical phased‐array antenna systems, and antenna arrays that do not employ spherical harmonics explicitly.